Application Of Kansei Structure In The Design Process For Clothing - Shaari , N. (Universiti Malaysia Sarawak, UNIMAS, 2014)
Traditionally user has focused much on the usability of products. Mostly in product development the influence of a product has on the user has been described through customer’s satisfaction (1). These measures say little about the interaction between user and the artifact. Future product development enhances the application of mass customization. The tendencies in product development make it likely that many future products will be functional and fulfill the customer’s needs. One task for product development in this context is to be able to capture customer’s considerations and feelings of products and transfer these emotional aspects into excellent product design. Functionality, attractiveness, ease in use, affordability and safety are all attributes that are expected by the users in their everyday product. As the increase of customers’ self-determination, the designers need gain an acute insight into their psychology cognizance and requirement to develop new products. In product development, Kansei engineering is a new approach which translating human feelings into product design. It has played an important role in the field of design.